2019
DOI: 10.3390/biom9100570
|View full text |Cite
|
Sign up to set email alerts
|

The MMP-8 rs11225395 Promoter Polymorphism Increases Cancer Risk of Non-Asian Populations: Evidence from a Meta-Analysis

Abstract: This meta-analysis aimed to systematically review the evidence on cancer risk of the MMP-8 rs11225395 promoter polymorphism. Relevant studies published by 12 June 2019 were identified by systematically searching PubMed, Web of Science, Cochrane Library, CNKI and Wanfang databases. R programs and STATA software were used to calculate odds ratio (OR) and 95% confidence interval (CI). In total, 7375 cancer samples and 8117 controls were included by integrating 15 case-control data sets. Pooled estimates from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…The allelic frequency of the A variant in the general population ranges from 18 to 45%, according to the different populations studied, with the highest prevalence in the European and Mexican populations (available at (accessed on 3 February 2022). This variant has been previously associated with many different conditions such as cancer [ 33 , 34 ], aggressive periodontitis [ 35 ], recurrent pregnancy loss [ 36 ], and inflammation in atherosclerosis [ 32 ]. In all these studies, Hardy–Weinberg was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…The allelic frequency of the A variant in the general population ranges from 18 to 45%, according to the different populations studied, with the highest prevalence in the European and Mexican populations (available at (accessed on 3 February 2022). This variant has been previously associated with many different conditions such as cancer [ 33 , 34 ], aggressive periodontitis [ 35 ], recurrent pregnancy loss [ 36 ], and inflammation in atherosclerosis [ 32 ]. In all these studies, Hardy–Weinberg was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, a meta-analysis was conducted by Feng et al to address the inconsistent results from various studies investigating the association of MMP-8 rs11225395 genotype with different types of cancer, including those mentioned previously. The meta-analysis revealed no association between MMP-8 rs11225395 genotype and overall cancer risk worldwide (30). Based on the current available evidence, it is tentatively concluded that there may be an elevated cancer risk associated with MMP-8 rs11225395 genotype in non-Asian populations, while no association has been found in Asian populations (30).…”
Section: Discussionmentioning
confidence: 92%
“…More recently, it has been shown (7,18) that specific polymorphisms in the MMP-9 and TIMP-2 genes potentially increase the risk of developing varicose veins in patients. Vein remodeling and associated gene expression were also studied, but the results did not correlate with the development and severity of PTS [5,12].…”
Section: Research Results and Discussionmentioning
confidence: 99%